Characterization of H type 1 and type 1 N-acetyllactosamine glycan epitopes on ovarian cancer specifically recognized by the anti-glycan monoclonal antibody mAb-A4. - Choo,M; Tan,HL; Ding,V; Castangia,R; Belgacem,O; Liau,B; Hartley-Tassell,L; Haslam,SM; Dell,A; Choo,A (Journal of Biological Chemistry, 2017)
Cancer-specific glycans of ovarian cancer are promising epitopes for targeting with monoclonal antibodies (mAb). Despite their potential, structural characterization of these glycan epitopes remains a significant challenge in mAb preclinical development. Our group generated the monoclonal antibody mAb-A4 against human embryonic stem cells (hESC), which also bound specifically to N-glycans present on 11 out of 19 ovarian cancer (OC) and 8 out of 14 breast cancer cell lines tested. Normal cell lines and tissue were unstained by mAb-A4. To characterize the N-linked glycan epitopes on OC cell lines targeted by mAb-A4, we used glycosidases, glycan microarray, siRNA and advanced high-sensitivity matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). The mAb-A4 epitopes were found to be Fuc α1-2Galβ1-3GlcNAcβ (H Type 1) and Galβ1-3GlcNAcβ (Type 1 LacNAc). These structures were found to be present on multiple proteins from hESC and OC. Importantly, endo-β-galactosidase coupled with MALDI-MS allowed these two epitopes, for the first time, to be directly identified on the polylactosamines of N-glycans of SKOV3, IGROV1, OV90 and OVCA433. Furthermore, siRNA knockdown of B3GALT5 expression in SKOV3 demonstrated that mAb-A4 binding was dependent on B3GALT5, providing orthogonal evidence of the epitopes' structures. The recognition of oncofetal H Type 1 and Type 1 LacNAc on OC by mAb-A4 is a novel and promising way to target OC and supports the theory that cancer can acquire stem-like phenotypes. We propose that the orthogonal framework used in this work could be the basis for advancing anti-glycan mAb characterization.